ILLEGITIMATE TASK DAN IMPLIKASINYA TERHADAP KEPUASAN KERJA SERTA COUNTERPRODUCTIVE WORK BEHAVIOR DOSEN USN KOLAKA - Suryani, Suryani; Wonua, Almansyah Rundu; Astaginy, Niar (BENING, 2025)
This study examines the impact of illegitimate tasks on job satisfaction and counterproductive work behavior among lecturers at Universitas Sembilanbelas November (USN) Kolaka. Utilizing an explanatory research design with a quantitative approach, data were gathered through questionnaires. The study involved 317 lecturers, With a total of 177 respondents, the sample was selected using Slovin’s formula and a stratified random sampling method. Data analysis was carried out using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through SmartPLS 4.0. The findings reveal that illegitimate tasks have a significant negative impact on job satisfaction while exerting a significant positive influence on counterproductive work behavior